A method for batch preparation of Co9S8-MoS2-nitrogen-doped carbon nanosheet negative electrode material
Co9S8-MoS2-nitrogen doped carbon nanosheet composite material was prepared in batches by salt template-assisted synthesis method, which solved the problem of volume expansion and capacity attenuation of sodium ion negative electrode material during sodium ion diffusion, and achieved efficient preparation of the material and excellent electrochemical properties.
Patent Information
- Application Number
- CN202411034698.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-31
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2044-07-31
AI Technical Summary
The negative electrode materials of existing sodium ion batteries are prone to volume expansion and capacity attenuation during the diffusion of sodium ions, and the synthesis process of bimetal sulfide heterostructure materials is complicated and difficult to mass production.
The salt template assisted synthesis method is used to mix the soluble raw material with the salt template liquid phase evenly, and then sinter it at a specific temperature to obtain the Co9S8-MoS2-nitrogen doped carbon nanosheet composite material. This method is simple and has mild conditions, and is suitable for large-scale production.
It realizes the efficient preparation of Co9S8-MoS2-nitrogen doped carbon nanosheet composite material, with excellent conductivity and reversible specific capacity, and is suitable for sodium ion battery negative electrode materials.
Smart Images

Figure CN118811865B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of transition metal sulfide negative electrode materials, and more specifically, to a method for batch preparing Co9S8-MoS2-nitrogen-doped carbon negative electrode materials. Background Art
[0002] At present, lithium-ion batteries, as a new type of energy storage device, have the advantages of high energy density and excellent cycle performance, and are widely used in daily life. However, limited resources can hardly meet the growing demand. In contrast, sodium-ion batteries are abundant in resources, low in cost, high in safety, and have a similar working principle to lithium-ion batteries. They are one of the promising alternatives to lithium-ion batteries. Unfortunately, the larger radius and higher potential of sodium ions make the diffusion kinetics of sodium-ion batteries slow. For traditional negative electrode materials, the continuous penetration of sodium ions will lead to significant volume expansion, resulting in serious capacity decay. Therefore, how to design negative electrode materials suitable for sodium-ion batteries is one of the problems that need to be solved urgently.
[0003] Among various negative electrode materials, transition metal sulfides have excellent sodium storage performance, especially MoS2, which has excellent theoretical capacity and has gradually become a popular material in current research. However, in practical applications, MoS2 has poor conductivity and serious agglomeration tendency, which increases the diffusion path of sodium ions. In addition, the conversion reaction between MoS2 and sodium ions will cause significant volume expansion and capacity attenuation, which seriously hinders its development.
[0004] Many studies have shown that constructing bimetallic sulfide heterostructures is an effective strategy to accommodate huge internal stress changes and ensure structural integrity. The synergistic effect and interfacial interaction between the components of the heterostructure can establish an internal electric field, promote the migration rate within the interface of the bimetallic sulfide, and also regulate the internal structure to provide more active sites for the storage of sodium ions, thereby improving the electrochemical performance.
[0005] However, among the many current methods for synthesizing bimetallic sulfide heterostructure materials, relatively complex multi-step synthesis processes are required, or mass production is impossible due to the particularity of the process, such as sintering the raw materials after hydrothermal reaction or adding the raw materials to carbon cloth and then sintering reaction, etc. This limits the large-scale preparation of bimetallic sulfide materials and thus limits their development in industry. Summary of the invention
[0006] Based on the above technical problems existing in the prior art, the present invention provides a method for batch preparation of Co9S8-MoS2-nitrogen-doped carbon nanosheet negative electrode materials. The method utilizes a salt template to assist in the synthesis of a composite material. The Co9S8-MoS2-nitrogen-doped carbon nanosheet composite material is obtained by evenly mixing a soluble raw material and a salt template liquid phase and then sintering them at a specific temperature. The method has a simple process, mild conditions, and a high yield, and is suitable for large-scale production of Co9S8-MoS2-nitrogen-doped carbon nanosheet composite materials.
[0007] In order to achieve the above object, the technical solution of the present invention is as follows:
[0008] A method for batch preparing Co9S8-MoS2-nitrogen-doped carbon nanosheet negative electrode material comprises the following steps:
[0009] S1. Add a soluble molybdenum source, a cobalt source, a carbon source, a sulfur source and a salt into water and mix them evenly; then dry them to obtain a precursor material;
[0010] S2, grinding the precursor material, and then sintering it at a temperature of 700-800° C. under a protective atmosphere, and naturally cooling it to room temperature to obtain a product;
[0011] S3. Wash the product obtained in step S2 with deionized water and ethanol, and dry it to obtain the Co9S8-MoS2-nitrogen-doped carbon negative electrode material.
[0012] In some embodiments, the molar ratio of the molybdenum source, cobalt source, carbon source, and sulfur source is 2.24:0.42-1.68:3.3-16.7:11; the mass ratio of the total mass of the molybdenum source, cobalt source, carbon source, and sulfur source to the mass of the salt is 1:0.7-1.5.
[0013] In some embodiments, the molybdenum source is at least one of ammonium molybdate heptahydrate, ammonium tetramolybdate, and molybdenum chloride.
[0014] In some embodiments, the sulfur source is at least one of thiourea and l-cysteine.
[0015] In some embodiments, the carbon source is at least one of glucose and citric acid.
[0016] In some embodiments, the cobalt source is at least one of cobalt chloride and cobalt nitrate.
[0017] In some embodiments, the salt is at least one of sodium chloride and potassium chloride.
[0018] In some embodiments, in step S2, the protective atmosphere is at least one of an argon atmosphere and a helium atmosphere.
[0019] In some embodiments, in step S1, the drying temperature is 60-100°C.
[0020] In some embodiments, in step S2, the temperature is increased to the sintering temperature at a rate of 1-10°C / min.
[0021] In some embodiments, in step S2, the sintering time is 1-2 hours.
[0022] In some embodiments, in step S3, the drying temperature is 60-80°C.
[0023] In some embodiments, the method comprises the following steps:
[0024] S1. Weigh a soluble molybdenum source, a cobalt source, a carbon source, a sulfur source and a salt, add them into water, mix them evenly, and dry them at a temperature of 60-100° C. to obtain a precursor material;
[0025] S2, grinding the precursor material uniformly, and then sintering it at 700-800° C. for 1-2 h under a protective atmosphere, and then naturally cooling it to room temperature to obtain a product;
[0026] S3. Wash the product obtained in step S2 with deionized water and ethanol at least once respectively, and then dry it at a temperature of 60-100° C. to obtain the Co9S8-MoS2-nitrogen-doped carbon negative electrode material.
[0027] The present invention also provides a Co9S8-MoS2-nitrogen-doped carbon nanosheet negative electrode material obtained by the method of any of the above embodiments.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] The present invention utilizes salt templates to assist in synthesizing nanosheet composite materials. After uniformly mixing a soluble raw material and a salt template liquid phase, sintering them at a specific temperature, and then washing to remove the salt template, a Co9S8-MoS2-nitrogen-doped carbon nanosheet composite material can be obtained. In the composite material, Co9S8 and MoS2 nanoparticles are distributed in the nitrogen-doped carbon nanosheet skeleton, and the nitrogen-doped carbon nanosheets are interconnected to form a flower-like structure. The composite material obtained by the method of the present invention has high purity and is applied as a negative electrode material in an electrochemical energy storage device. It has a continuous ion / electron transfer channel and excellent conductive performance. In addition, the flower-like structure formed by the nanosheets can increase the contact and penetration between the composite material and the electrolyte, so that the composite material exhibits excellent reversible specific capacity and rate performance.
[0030] The synthesis method of the present invention directly mixes the raw materials evenly and then sinters and washes them, and the composite material can be obtained without hydrothermal reaction or other complicated process operations. The method is simple, efficient, low-cost, has simple equipment requirements, is easy to operate, has strong repeatability, and has a high yield. It can be prepared on a large scale and is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a scanning electron microscope image of the sample obtained in Example 1;
[0032] Figure 2 TEM image of the sample obtained in Example 1;
[0033] Figure 3 Element composition diagram of a local area of the sample obtained in Example 1;
[0034] Figure 4 is the X-ray diffraction pattern of the sample obtained in Example 1;
[0035] Figure 5 The cyclic voltammetric characteristics and the first three charge and discharge curves of the sample obtained in Example 1; wherein (a) is a cyclic voltammetric characteristic diagram, and (b) is a first three charge and discharge curve diagram;
[0036] Figure 6 This is the cycle performance diagram of the sample obtained in Example 1;
[0037] Figure 7 The first three charge and discharge curves and cycle performance diagrams of the sample obtained in Example 2; wherein (a) is the first three charge and discharge curves, and (b) is the cycle performance diagram;
[0038] Figure 8 The first three charge and discharge curves and cycle performance diagrams of the sample obtained in Example 3; wherein (a) is the first three charge and discharge curves, and (b) is the cycle performance diagram;
[0039] Fig. 9 This is the cycle performance diagram of the sample obtained by the method of Comparative Example 1. DETAILED DESCRIPTION
[0040] Many specific details are set forth in the following description to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar modifications without violating the connotation of the present invention, so the present invention is not limited to the specific implementation disclosed below.
[0041] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0042] Example 1
[0043] A method for batch preparing Co9S8-MoS2-nitrogen-doped carbon nanosheet composite material comprises the following steps:
[0044] 0.4 g of ammonium molybdate heptahydrate, 0.8 g of thiourea, 0.5 g of glucose and 2.0 g of sodium chloride were dissolved in 40 ml of deionized water; then 0.2 g of cobalt chloride tetrahydrate was added and stirred at room temperature to mix the raw materials evenly to obtain a mixed solution; the mixed solution was placed in an oven at 80°C for 24 h, the dried sample was fully ground and transferred to a ceramic container, and heated at 5°C min under the protection of an argon atmosphere. -1 The temperature was raised to 700°C at a heating rate of , and sintered at 700°C for 2 hours; after the sintering was completed, it was cooled to room temperature and the product was collected; the collected product was washed alternately with deionized water and ethanol several times (3-4 times), and then dried in a vacuum oven at 60°C to obtain a Co9S8-MoS2-nitrogen-doped carbon nanosheet composite material.
[0045] The obtained composite material was tested, and the scanning electron microscopy results and transmission electron microscopy results were as follows: Figure 1 and Figure 2 The element composition diagram of the local area is shown in Figure 3 The X-ray diffraction pattern is shown in Figure 4 shown.
[0046] Depend on Figure 1 and Figure 2 It can be observed that Co9S8 and MoS2 nanoparticles are uniformly dispersed in the nitrogen-doped carbon nanosheet skeleton, and the nanosheet skeletons are interconnected to present a flower-like structure.
[0047] like Figure 3 , we can see that the different contents of Mo, Co, S, C, and N elements in the composite material are evenly distributed, the N element content is the lowest, and the S element content is the highest; Figure 4 The peaks of Co9S8 and MoS2 crystals can be observed.
[0048] The composite material sample obtained in this example was made into a battery according to the following method:
[0049] The composite material, acetylene black and alginic acid were mixed in a mass ratio of 7:2:1, added into ionized water, and fully ground to form a uniform slurry; the slurry was evenly coated on a copper foil, dried in an oven at 60°C for 6 hours, and then cut into discs with a diameter of 14 mm, and then the discs were placed in a vacuum drying oven and dried at 120°C for 12 hours to remove surface water and oxygen to obtain pole pieces; metallic sodium was used as a counter electrode and glass fiber (GF / D Whatman) was used as a diaphragm; 1M sodium perchlorate was dissolved in ethylene carbonate / propylene carbonate (1:1 vol%), and 5% fluoroethylene carbonate was added as an electrolyte; under the protection of argon, a CR2032 button half-cell was assembled in a glove box.
[0050] After the assembled battery was left to stand for 12 hours, constant current charge and discharge tests were performed on the CT3002A blue power test system, with a voltage range of 0.01 to 3 V and a current density of 0.2 Ag. -1 , the test results are as follows Figure 5-Figure 6 shown.
[0051] like Figure 5 As shown in Figure (a), in the initial cathode scan, the strong peak at 0.73V is the process of MoS2 reacting with sodium ions to generate Mo and Na2S, and the peak at 0.37V is the process of Co9S8 reacting with sodium ions to generate Co and Na2S. In the initial anodic scan, the peak at 1.7V corresponds to the process of Na x The process of extracting sodium ions in Co9S8, the peak at 1.8V belongs to Na x During the de-sodiumization process of MoS2, it can be observed that the second cycle and the third cycle curves are basically overlapped, indicating that the composite material obtained in this embodiment has good cycle stability when used as the negative electrode of a sodium ion battery. Figure 5 As shown in Figure (b), the first charge / discharge specific capacity is 595.4 / 756.8 mAh g -1 , with a higher charge and discharge specific capacity.
[0052] Figure 6 The cycle performance diagram of the composite material of this embodiment is shown. It can be seen that after 100 cycles, the charge / discharge capacity of the composite material remains at 480 / 482.5 mAh g -1 , showing excellent cycle stability.
[0053] Example 2
[0054] A method for batch preparing Co9S8-MoS2-nitrogen-doped carbon nanosheet composite material comprises the following steps:
[0055] 0.4 g of ammonium molybdate heptahydrate, 0.8 g of thiourea, 0.5 g of glucose and 2.0 g of sodium chloride were dissolved in 40 ml of deionized water; then 0.1 g of cobalt chloride tetrahydrate was added and stirred at room temperature to mix the raw materials evenly to obtain a mixed solution; the mixed solution was placed in an oven at 80 °C for 24 h, the dried sample was fully ground and transferred to a ceramic container, and heated at 5 °C min under argon atmosphere. -1 The temperature was raised to 700°C at a heating rate of , and sintered at 700°C for 2 hours; after the sintering was completed, it was cooled to room temperature and the products were collected; the collected products were washed several times with deionized water and ethanol respectively, and then dried in a vacuum oven at 60°C to obtain a Co9S8-MoS2-nitrogen-doped carbon nanosheet composite material.
[0056] The composite material obtained in Example 2 was made into a CR2032 type button half-cell according to the method described in Example 1.
[0057] After the assembled battery was left to stand for 12 hours, constant current charge and discharge tests were performed on the CT3002A blue power test system, with a voltage range of 0.01 to 3 V and a current density of 0.2 Ag. -1 , test resultsru Figure 7 shown.
[0058] Figure 7 The first three charge and discharge curves and cycle performance diagrams of the composite material obtained in this embodiment are shown. Figure 7 As can be seen in Figure (a), the first charge / discharge specific capacities of the composite material of this embodiment are 499 / 618.1 mAh g -1 , with a higher charge and discharge specific capacity;
[0059] from Figure 7 As can be seen in Figure (b), the charge / discharge capacity of the composite material remains at 358.5 / 362.4 mAh g after 100 cycles. -1 , showing excellent cycle stability.
[0060] Example 3
[0061] A method for batch preparing Co9S8-MoS2-nitrogen-doped carbon nanosheet composite material comprises the following steps:
[0062] 0.4 g of ammonium molybdate heptahydrate, 0.8 g of thiourea, 0.1 g of glucose and 2.0 g of sodium chloride were dissolved in 40 ml of deionized water; then 0.2 g of cobalt chloride tetrahydrate was added and stirred at room temperature to mix the raw materials evenly to obtain a mixed solution; the mixed solution was placed in an oven at 80°C for 24 h, the dried sample was fully ground and transferred to a ceramic container, and heated at 5°C min under argon atmosphere. -1The temperature was raised to 700°C at a heating rate of , and sintered at 700°C for 2 hours; after the sintering was completed, it was cooled to room temperature and the product was collected; the collected product was washed alternately with deionized water and ethanol several times, and then dried in a vacuum oven at 60°C to obtain a Co9S8-MoS2-nitrogen-doped carbon nanosheet composite material.
[0063] The material obtained in Example 3 was made into a CR2032 type button half-cell according to the method described in Example 1.
[0064] After the assembled battery was left to stand for 12 hours, constant current charge and discharge tests were performed on the CT3002A blue power test system, with a voltage range of 0.01 to 3 V and a current density of 0.2 Ag. -1 , the test results are as follows Figure 8 shown.
[0065] Figure 8 The first three charge and discharge curves and cycle performance diagram of the composite material obtained by the method of this embodiment are shown.
[0066] from Figure 8 As can be seen in Figure (a), the initial charge / discharge specific capacities of the composite material are 432.6 / 566.4 mAh g -1 , with a higher charge and discharge specific capacity;
[0067] from Figure 8 As can be seen in Figure (b), the charge / discharge capacity of the composite material remained at 301.4 / 303.2 mAh g after 100 cycles. -1 , showing excellent cycle stability.
[0068] Comparative Example 1
[0069] A method for preparing a molybdenum disulfide-cobalt sulfide-carbon ternary composite in-situ electrode comprises the following steps:
[0070] At room temperature, MoCl5, CoCl2·6H2O, Tx-100 and thiourea are dissolved in 2.7 mL of N,N-dimethylformamide solution to obtain a precursor solution; wherein the total concentration of MoCl5 and CoCl2·6H2O is 400 mM, the concentration ratio of the two substances is 1:1, the amount of Tx-100 is 0.3 mL, and the concentration of thiourea is 1000 mM; carbon paper is soaked in the precursor solution for 30 min and then taken out, placed in an oven and dried at 80° C. for 10 min, and then the precursor is evenly dripped on the carbon paper, and continued to dry for 30 min; the coated carbon paper is placed in a tubular furnace, reacted at 600° C. for 1 h under an Ar atmosphere, taken out after natural cooling, cut into discs with a diameter of 14 mm, and a CR2032 button half-battery is made according to the method of Example 1.
[0071] After the assembled battery was left to stand for 12 hours, constant current charge and discharge tests were performed on the CT3002A blue power test system, with a voltage range of 0.01 to 3 V and a current density of 0.2 Ag. -1 , the test results are as follows Fig. 9 shown.
[0072] Fig. 9 The cycle performance diagram of the composite material obtained in this embodiment is shown in FIG. Fig. 9 It can be seen that the first cycle charge / discharge capacity of the composite material is 398 / 474.7 mAh g -1 After 100 cycles, the charge / discharge capacity remained at 332.3 / 332.3 mAh g -1 .
[0073] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0074] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for batch preparation of Co9S8-MoS2-nitrogen-doped carbon nanosheet negative electrode material, characterized in that: The following steps are involved: 0.4 g of ammonium molybdate heptahydrate, 0.8 g of thiourea, 0.5 g of glucose and 2.0 g of sodium chloride were dissolved in 40 ml of deionized water; then 0.2 g of cobalt chloride tetrahydrate was added and stirred at room temperature to mix the raw materials evenly to obtain a mixed solution; the mixed solution was placed in an oven at 80°C for 24 h, the dried sample was fully ground and transferred to a ceramic container, and heated at 5°C min under the protection of an argon atmosphere. -1 The temperature was raised to 700°C at a heating rate of 100°C and sintered at 700°C for 2h; After sintering, the product was cooled to room temperature and collected; The collected product was washed alternately with deionized water and ethanol for 3-4 times and then dried in a vacuum oven at 60 °C to obtain a Co9S8-MoS2-nitrogen-doped carbon nanosheet composite material.
2. The negative electrode material obtained by the preparation method according to claim 1.